Alternate wetting and drying irrigation at tillering stage enhances the heat tolerance of rice by increasing sucrose and cytokinin content in panicles - Gao, Ti; Xie, Keran; Hu, Qiuqian; Wu, Chao; Wang, Zhenmei; Wang, Wencheng; Xiong, Dongliang; Huang, Jianliang; Peng, Shaobing; Cui, Kehui (Frontiers in Plant Science, 2025)
High temperature events have occurred frequently in recent years under global warming conditions. High temperature during panicle initiation (PI) poses significant negative impacts on rice grain yield. Alternate wetting and drying irrigation (AWD) is widely adopted in rice cultivation. Here, to investigate the alleviating effect of AWD on heat damage to rice (Oryza sativa L.), we selected four rice varieties with different high-temperature resistance (Liangyoupeijiu, IR64, Huanghuazhan, Shanyou 63), two irrigation treatments at the tillering stage including AWD and continuous flooding (CF) and two temperature treatments at the PI stage (high daytime temperature, HDT; and control temperature, CK) were applied. HDT significantly reduced the yield of all four varieties except for Shanyou 63, primarily by decreasing the spikelet fertility and spikelet number, while AWD significantly improved the two traits under HDT. Moreover, HDT reduced the photosynthetic rate, increased the starch content in leaves and stems, and decreased the transport of sucrose to panicles. AWD reduced the panicle temperature, promoted sucrose synthesis in leaves, increased sucrose content and sucrose hydrolase activity in panicles under HDT. HDT also increased the content of abscisic acid and decreased that of cytokinins (CTKs), indole-3-acetic acid (IAA), and gibberellins (GAs) in panicles under CF. AWD increased the expression of CTK biosynthesis genes (IPT, CYP735A, LOG) and decreased that of CTK degradation gene CKX in roots and panicles under HDT, while enhanced the xylem sap flow rate and contents of CTKs, IAA, and GAs in panicles. Furthermore, AWD exhibited a more pronounced alleviating effect on HDT damage in heat-sensitive varieties than in heat-tolerant varieties. In summary, AWD leads to lower panicle temperature and higher photosynthetic rate, sucrose content, and CTK level in panicles, which together enhance the heat tolerance at the PI stage, and therefore is a sustainable and feasible strategy to mitigate heat-induced yield loss in rice.